Traffic Card Media with Jigsaw Method: Improving Knowledge, Attitude, and Sanitation Hygiene for Stunting Prevention - Nur Juliana; Wa Ode Megasari; Rasniah Sarumi; Elna Sari; Wahidah Rohmawati; Muhammad Ihsan Tamsri (Asia Pacific Journal of Management and Education (APJME), 2025)
Indonesia continues to face significant challenges in reducing stunting rates, particularly in rural areas. The primary contributing factors include a lack of parental knowledge, unsupportive lifestyle attitudes, and poor environmental sanitation. Nutrition education plays a crucial role in raising mothers' awareness of stunting. This study sought to evaluate mothers’ knowledge, attitudes, and sanitation hygiene practices regarding toddlers aged 24 to 60 months while incorporating traffic card media and the jigsaw method in group discussions to strengthen these factors for effective stunting prevention. It adopts a quantitative research design with a one-group pretest-posttest approach. The study was conducted in the working area of the Wapunto Health Center from July to October 2023. A simple random sampling technique was used, involving 21 respondents. Data were analyzed using a non-parametric Wilcoxon test. The pretest and posttest average scores for each variable were as follows: knowledge (67.95 to 81.95), attitude (61.43 to 80.05), and sanitation hygiene (80.95 to 90.95), indicating an overall improvement. The p-values were 0.05 for all variables, with knowledge and attitude each at p = 0.000 and sanitation hygiene at p = 0.002, demonstrating a significant effect of the intervention. Traffic card media proves to be an effective educational tool for increasing public awareness of stunting prevention by improving knowledge, attitudes, and sanitation hygiene practices.